2011
DOI: 10.1109/tvlsi.2010.2055247
|View full text |Cite
|
Sign up to set email alerts
|

Fast Placement-Aware 3-D Floorplanning Using Vertical Constraints on Sequence Pairs

Abstract: We present a placement-aware 3-D floorplanning algorithm that considers 3-D-placement of logic gates inside modules for wirelength minimization. It allows designers to introduce and evaluate an assignment of vertically-aligned parts of the same module to different device layers. A set of vertical constraints is derived on sequence pairs of different device layers that reduces the solution space, and a fast packing algorithm with vertical constraints enables quick floorplan evaluation. Experimental results on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…We modified the 3D-FVC floorplanner presented in [9] to perform TSV island packing together with packing of circuits' blocks. 3D FVC uses Sequence Pair (SP) representation and is based on Evolutionary Algorithm (EA).…”
Section: D Floorplanning Algorithmmentioning
confidence: 99%
“…We modified the 3D-FVC floorplanner presented in [9] to perform TSV island packing together with packing of circuits' blocks. 3D FVC uses Sequence Pair (SP) representation and is based on Evolutionary Algorithm (EA).…”
Section: D Floorplanning Algorithmmentioning
confidence: 99%
“…There are various approached for 3-D floorplanning that consider TSV locations proposed in the literature [6]- [9]. Some of the early approaches [6] treated TSVs as points ignoring the impact of TSV sizes on area and wirelength.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the early approaches [6] treated TSVs as points ignoring the impact of TSV sizes on area and wirelength. Tsai et al [7] considered TSVs as cells, and observed the impact on the area and wirelength of the floorplan but did not discuss power dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of a sophisticated 3D environment sometimes requires several years of work by a team of specialists, which is both very expensive and time consuming. That is why, the automatic generation of three-dimensional (3D) layout design solutions gains more and more attention, especially in the field of floorplanning of integrated circuits design [22] and architectural design [20].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, floor plans are divided into two categories: the slicing and the non-slicing structure. A slicing floor plan is obtained by recursively bisecting a rectangle using a horizontal and/or vertical line [22]. The solution space is much smaller than in a non-slicing case which implies simpler data structures representation and faster runtime.…”
Section: Introductionmentioning
confidence: 99%